Investigating the Effect of Economic Risk Components on the Development of Sukuk Market in Iran (Nonlinear Autoregressive Distributed Lag Model Approach) - Bahman Khanalizadeh; Ashkan Rahimzadeh; Mohammad Dalmanpour; Majid Afsharirad (تحقیقات مالی اسلامی (پیوسته))
The main purpose of this research is to investigate the effects of economic risk components along with economic complexity on the development of sukuk market in Iran during the period of 1389.1-1401.4. The results of the estimation of the model using the WALD test and NARDL test show that the unexpected positive and negative shocks of all research variables have asymmetric effects on the development of the sukuk market. The positive shock of budget balance risk has the greatest effects on the development of the sukuk market in the short and long term. The positive shock of inflation risk in the long and short term has positive effects on the development of the sukuk market. The positive shock of the GDP risk has positive effects on the development of the sukuk market, but its negative shock in the long term is far more than other economic risks. The effects of positive and negative shocks of real economic growth risk on the development of sukuk market are less than other components of economic risk. Also, the short-term and long-term effects of economic complexity on the development of the sukuk market are positive.